NOISE INTENSITY, BLOOD PRESSURE, AND PULSE RATE IN TEXTILE INDUSTRY WORKERS - Chahyadhi, Bachtiar; Widjanarti, Maria Paskanita; Ada', Yeremia Rante; Suratna, Farhana Syahrotun Nisa; Wijayanti, Reni (Placentum: Jurnal Ilmiah Kesehatan dan Aplikasinya, 2022)
Background: Noise intensity that exceeds Threshold Limit Value (TLV) can give impacts on non-auditory on the workers in a factory, in the form of an increase in blood pressure and pulse rate. Currently, health problems due to noise have caused the company’s total loss to reach 300 billion dollars due to absenteeism rate, decreased productivity, and treatment for occupational diseases. Research in Indonesia, especially the textile industry in the city of Surakarta, shows that noise from weaving machines with an intensity above 100 dBA affects blood pressure and pulse rate. This research was conducted at textile industry in Surakarta, one of the largest textile companies in Surakarta where the company has not been able to overcome the problem of noise intensity that exceeds the TLV which has the potential to cause blood pressure and pulse disturbances, and even decreased hearing function. This study aims to determine the relationship between noise intensity with blood pressure and pulse rate in textile industry workers. Method: This research is a correlation study, which is connecting the measurement variables of noise intensity with blood pressure and pulse rate. The sample in this study were 30 female workers in the weaving division who met the inclusion and exclusion criteria. The instruments used in measuring noise were sound level meters and sphygmomanometers. Data analysis used the Pearson correlation test to determine the relationship between noise intensity with blood pressure and pulse rate disturbances.Result: The study showed significant correlation between noise intensity and pulse rate with a p value of 0.029, but noise intensity with blood pressure disturbances does not correlate, with a p value of 0.443.Conclusion: There is a relationship between noise intensity and pulse rate of the workers in a factory.